2019
DOI: 10.3390/ma12203279
|View full text |Cite
|
Sign up to set email alerts
|

“In Vitro” Study About Variables that Influence in Arch Friction with Conventional and Self-Ligating Brackets

Abstract: Many advantages have been described surrounding self-ligating (SL) brackets compared to metallic conventional ligating (CL) brackets, such as: Less total treatment time, alignment efficiency, patient comfort, plaque retention, and low friction. The objective of this in vitro simulation was to know the variables that affect arch displacement in CL and SL brackets—active (ASL) and passive (PSL)—and analyze if static friction values are affected by bracket design, arch wire section, kind of ligature, and use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(43 reference statements)
0
1
0
3
Order By: Relevance
“…Los brackets convencionales requieren métodos de ligadura para mantener el arco dentro de la ranura de los brackets, estos son de tipo elástico y metálica, la ligadura elástica se asocia con valores más altos de fricción debido a que tiene un mayor contacto con la superficie de los arcos, mientras que la ligadura metálica podría producir una mayor o menor fricción que depende de la fuerza que utilice el ortodoncista (Moyano et al, 2019).…”
Section: Método De Ligaduraunclassified
See 2 more Smart Citations
“…Los brackets convencionales requieren métodos de ligadura para mantener el arco dentro de la ranura de los brackets, estos son de tipo elástico y metálica, la ligadura elástica se asocia con valores más altos de fricción debido a que tiene un mayor contacto con la superficie de los arcos, mientras que la ligadura metálica podría producir una mayor o menor fricción que depende de la fuerza que utilice el ortodoncista (Moyano et al, 2019).…”
Section: Método De Ligaduraunclassified
“…La superficie del arco de alambre tales como la rugosidad y la topografía puede influenciar en el coeficiente de fricción durante el deslizamiento. La rugosidad de la superficie de los materiales dentales es muy importante, ya que contribuye al área de contacto de la superficie y, por lo tanto, tiene un impacto en la conducta corrosiva y la biocompatibilidad del material, además la rugosidad puede influir en la acumulación de placa dentobacteriana, lo que contribuye a aumentar la fricción y la salud biológica (Moyano et al, 2019).…”
Section: Arco De Alambreunclassified
See 1 more Smart Citation
“…Moreover, research showed that materials do not differ in ranking according to the level of their dynamic and static friction component [ 18 ]—the static proved to be higher than the kinetic friction [ 43 ]. There have been a few studies in recent years that focused on static friction [ 27 , 35 ] or include measurements of static friction [ 43 ]. However, we thought that focusing on the measurement of dynamic friction is a more suitable basis for comparison of friction as it is easier to reproduce, even if clinical conditions are insufficiently simulated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%